Pulmonary hypertension topics. (October 2012) - Mathai, Stephen C; Girgis, Reda E
The International Society for Heart and Lung Transplantation, 32nd Annual Meeting and Scientific Sessions Prague, Czech Republic, 18–21 April 2012 Interest in pulmonary hypertension (PH) continues to grow within the International Society for Heart and Lung Transplantation (ISHLT). The PH program at the 32nd annual meeting held on 18–21 April 2012 in Prague, Czech Republic, was particularly strong, with 56 accepted abstracts and five symposia dealing with PH and right ventricular function. In this report, we will summarize selected oral abstract presentations dealing with a broad array of topics on PH and right ventricular function. These include original research on registries, prognosis, disease management, clinical trials, novel therapies, echocardiographic assessments and exercise hemodynamics.